Anatomical bone differences between the male and female faces: A narrative literature review (Research, Society and Development, 2025)
The human face is fundamental for communication, identity, and social interaction, composed of 14 bones that support physiological functions. Throughout evolution, a reduction in prognathism and tooth size was observed, resulting in more retruded facial structures, reflecting dietary, behavioral, and cultural adaptations. In this context, facial sexual dimorphism is a key element for understanding structural differences between men and women, with clinical, anthropological, and forensic relevance. This narrative review aimed to analyze these skeletal particularities in the upper, middle, and lower thirds of the face, considering anatomical and aesthetic implications. The methodology consisted of searching scientific articles in the PubMed and SciELO databases. Results show that men exhibit greater glabellar projection, frontal robustness, and wider orbits, while women display smoother contours and smaller bone dimensions in the upper third. In the middle third, men have larger zygomatic measurements and narrower nasal cavities, whereas women present wider piriform openings, with relevant ethnic variations. In the lower third, the male mandible is more angled and robust, with greater projection and cortical thickness. These differences guide orofacial harmonization procedures, where feminization softens structures and masculinization emphasizes contours. It is concluded that skeletal anatomical differences reflect a complex interplay of evolutionary, functional, and aesthetic factors, whose understanding is essential for contemporary clinical, forensic, and scientific applications.